The Prehabilitation Radiotherapy Exercise, smoking Habit cessation and Balanced diet Study (PREHABS) protocol to explore the feasibility of embedding behavioural modifications into the clinical pathway for patients undergoing radical radiotherapy for lung cancer - Matthew Callister; Kevin Franks; Rachael L Murray; Jenny Hewison; Gillian Williams; Alison Boland; Emma Morgan; Carole Burnett; Cecilia Pompili; Janine Bestall; Shaunna Burke; Samuel Greenwood-Wilson; et al. (BMJ Open)
Methods and analysis The Yorkshire Cancer Research-funded Prehabilitation Radiotherapy Exercise, smoking Habit cessation and Balanced diet Study (PREHABS) (L426) is a single-centre prospective feasibility study to assess embedding behavioural changes into the radical radiotherapy pathway of patients with lung cancer. Feasibility will be assessed by measuring acceptability, demand and implementation. The duration of the study is 24 months. PREHABS has two workstreams: the intervention study and the theory of change (ToC) study.Intervention study: PREHABS will commence at the R-IDEAL phase 2 trial (exploratory) based on existing evidence and includes support for smoking cessation, increasing activity and dietary well-being. Patients undergoing radical radiotherapy for lung cancer will be recruited from the oncology department at Leeds Teaching Hospitals NHS Trust (LTHT). ToC study: to maximise the acceptability and adherence to the PREHABS, we will use a ToC approach to qualitatively explore the key barriers and enablers of implementing a tailored programme of ‘prehabilitation’. The PREHABS ToC study participants will be recruited from patients with lung cancer undergoing radical radiotherapy and staff from the LTHT oncology department.Analysis The primary endpoint analysis will report the number of participants and adherence to the study interventions. Secondary endpoints include continued engagement with study interventions post-treatment. The analysis will focus on descriptive statistics. Thematic analysis of the qualitative data from the ToC study will identify consensus on intervention optimisation and delivery.Ethics and dissemination On 12 May 2021, the Cambridge East Ethics Committee granted ethical approval (21/EE/0048). The study is registered in the National Institute for Health and Care Research (NIHR) portfolio. The results will be disseminated through publication in peer-reviewed scientific journals and presented at conferences.Trial registration number NIHR portfolio 48420.